Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-53698-x
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Artifacts in Single Molecule Localization Microscopy Analysis Arising from Pixel Quantum Efficiency Differences in sCMOS Cameras

Abstract: Optimal analysis of single molecule localization microscopy (SMLM) data acquired with a scientific Complementary Metal-Oxide-Semiconductor (sCMOS) camera relies on statistical compensation for its pixel-dependent gain, offset and readout noise. In this work we show that it is also necessary to compensate for differences in the relative quantum efficiency (RQE) of each pixel. We found differences in RQE on the order of 4% in our tested sCMOS sensors. These differences were large enough to have a noticeable effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…For algorithms that factor in multiplicative noise, the conversion factors that relate a set of ADUs to effective photons are required quantities. Extensive work on CCD (Young et al, 1998) and sCMOS (Babcock et al, 2019; Huang et al, 2013) sensors has demonstrated that statistical regression with a simplified model can effectively recover Poisson-like statistics for estimators that use multiplicative noise models. Given that a scientific camera produces an output signal S i at pixel i the signal components are defined as: where K i is the effective photon count, G i is the multiplicative gain factor on the Poisson-like signal, O i is the constant mean offset, and R i is an unbiased random electronic signal generated from the camera read noise.…”
Section: Resultsmentioning
confidence: 99%
“…For algorithms that factor in multiplicative noise, the conversion factors that relate a set of ADUs to effective photons are required quantities. Extensive work on CCD (Young et al, 1998) and sCMOS (Babcock et al, 2019; Huang et al, 2013) sensors has demonstrated that statistical regression with a simplified model can effectively recover Poisson-like statistics for estimators that use multiplicative noise models. Given that a scientific camera produces an output signal S i at pixel i the signal components are defined as: where K i is the effective photon count, G i is the multiplicative gain factor on the Poisson-like signal, O i is the constant mean offset, and R i is an unbiased random electronic signal generated from the camera read noise.…”
Section: Resultsmentioning
confidence: 99%
“…We replaced the camera noise data with our measurement or simulation. The NCS and MLE sCMOS use a gain map to correct FPN, which is considered to be not accurate enough [3, 15]. Therefore, instead of using the gain map, we used the measured gain value of the camera multiplying by the photon response map.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…We use photon response map to replace gain map and/or QE map, so that the calculation can be easier. Note that this treatment is accurate enough for photon signal calculation but would lead to a small bias in electron signal calculation [15]. We further analyze these noise maps by: 1) calculate the SD of relative offset map and photon response map to obtain DSNU and PRNU, respectively; 2) calculate the RMS of read noise map to obtain the amplitude of global read noise of the entire camera; 3) calculate the ratio of the SD to the RMS of the read noise to present RNNU.…”
Section: Characterization Of Scmos Noisementioning
confidence: 99%
See 1 more Smart Citation
“…For algorithms that factor in multiplicative noise, the conversion factors that relate a set of ADUs to effective photons are required quantities. Extensive work on CCD (Young et al, 1998) and sCMOS (Babcock et al, 2019;Huang et al, 2013) sensors has demonstrated that statistical regression with a simplified model can effectively recover Poisson-like statistics for estimators that use multiplicative noise models. Given that a scientific camera produces an output signal S i at pixel i the signal components are defined as:…”
Section: Camera Calibrationmentioning
confidence: 99%